Optimizing the operation of AIS (Automatic Identification System) in an effort to maintain shipping safety - Yudhi Setiyantara; Ningrum Astriawati; Yudhanita Pertiwi; Ade Chandra Kusuma; Thomas Wahyu Bagaskoro (Meteor STIP Marunda, 2023)
AIS stands for Automatic Identification System, which is a system that can provide automatic information about the data of a ship to another ship with a certain distance, how to operate AIS. The purpose of this research is to optimize the operation of AIS (Automatic Identification System) in an effort to maintain shipping safety on MV. Red Dahlia. This study uses a Mix Method approach with data collection methods using questionnaires, direct observation in the field, unstructured interviews and documentation. The results of the study show that AIS works using a very high frequency (VHF), which is between 156 – 162 MHz. By knowing the operation of the functions of navigation tools, it is very important, especially knowing the buttons contained in the AIS and their respective functions so that they can avoid the danger of collision with other ships or that can endanger navigation. From the results of the questionnaire, it was obtained that the average results of optimizing AIS operations to maintain sailing safety were 75.91% who said they strongly agreed, 17.27% said they agreed, and only 6.82% said they disagreed.